Theoretical Biosensor Design for Gold- PVA Surface Plasmon Resonance Layers - Kadhum, Farah Jawad; Saeed, Asrar Abdulmunem; AL-kadhemy, Mahasin F. Hadi; Al-Zuky, Ali A. Dawood; Al- Saleh, Anwar H. (Iraqi Journal of Science, 2021)
. Surface Plasmon Resonance (SPR) technology has been adapted to produce a sensitive optical sensor and Biosensor applications. Simulation analysis ( in Matlab) has been made for SPR for gold (Au) layer with thickness (40 nm) and Polyvinyl Alcohol (PVA) polymer with various thickness (10, 20, 30, 40, 50, 60, 70 and 80 nm) deposited on glass prism type D-ZLAF50_Dense lanthanum flint. The sensitive layer was air (n=1). The analysis was taken for different wavelengths from Ultra-Violet wavelength 100 nm to Near Infra- Red wavelength 1000 nm. The properties of Î¸SPR have been calculated from plotted reflectance against incident angle Î¸incid.. The SPR sensitivity (S) was calculated. The results give efficient detection in change of sensitive layer refractive index (0, 0.04, 0.08 and 0.12), and obtained the maximum sensitivity 207.5 for thickness of PVA 40 nm and 50 nm, âˆ†n= 0.08 at wavelength 800nm and 1000nm, respectively. The best sensitivity in visible region (700 nm) is 158.33 for thickness 20nm, âˆ†n= 0.12.